Dissemination of a dissonance-based body image promotion program in church settings: A preliminary controlled pilot study with adult women. (March 2021) - Blomquist, Kerstin K.; Hirsch, Katherine E.; Lomas, Elizabeth; Montgomery, Kathryn; Becker, Carolyn Black
Highlights: Dissonance-based body image program was adapted for women in church settings. Program improved body dissatisfaction risk factors and eating psychopathology. Peer delivery provided sustained improvements six-months post-intervention. Abstract: Adult women report significant body dissatisfaction yet are often overlooked in body image promotion programs. Although few venues afford opportune settings for intervening with adult women, the church serves as a regular meeting place for many in the South of the United States. This study tested a dissonance-based body image program, Reclaiming Beauty (RB), adapted for adult women in church settings. Six groups ( n = 30) were led by two trained church leaders (peer-led) and three groups ( n = 21) were led by a trained peer leader and a researcher (researcher-co-led). RB participants, aged 30–77 years ( M = 53.1 ± 12.7), completed assessments pre-intervention, immediately post-intervention, and 6 months post-intervention. Waitlist-controls ( n = 31) completed assessments at time intervals consistent with intervention participants. RB participants reported significantly decreased thin-ideal internalization, body surveillance, and eating psychopathology at post-intervention and at 6 months post-intervention relative to controls. RB participants also reported significantly increased body satisfaction immediately post-intervention relative to controls, but this was not significant at 6 months post-intervention. Peer-led groups outperformed researcher-co-led groups on body surveillance at 6 months, but RB conditions did not otherwise differ. Our findings provide preliminary support for the dissemination of a culturally-modified dissonance-based body image program to adult women in church settings.